Karakteristik Kewirausahaan - Lidya Rima Ranti; Fadillah Ramadhani .A; Rianti Simarmata (Pusat Riset dan Inovasi Nasional, 2024)
Entrepreneurship has become a major focus in economic and social development in various countries. This research aims to identify and analyze entrepreneurial characteristics that play a role in business success. Through qualitative and quantitative approaches, we explore factors such as innovation, motivation, creativity, self-confidence, honesty, and resilience to risk that influence entrepreneurial behavior. Our findings suggest that these characteristics are not only important for starting new businesses, but also for sustaining and growing existing businesses. The practical and theoretical implications of these findings are discussed, along with suggestions for further research in understanding the dynamics of entrepreneurship in a changing global context. This research provides valuable insights for practitioners, academics, and policymakers interested in promoting and supporting entrepreneurial development at the individual and organizational levels.